Normal Sections Calculation of Bending Reinforced Concrete and Fiber Concrete Elements - Kochkarev, Dmytro; Galinska, Tatyana; Tkachuk, Oleksandr (International Journal of Engineering and Technology, 2018)
The basic principles of the normal sections calculation of reinforced concrete and fiber reinforced concrete bending elements are considered. In the article the power and deformation methods of calculation of reinforced concrete and fiber concrete elements of rectangular cross-section are presented. The deformation model of the calculation of reinforced concrete and fiber concrete elements is presented in the framework of the method of calculation resistance of the section. This method makes possible from the common methodological positions to perform calculations of reinforced concrete and fiber concrete elements. Namely, to select reinforcement and to determine the carring capacity. The proposed deformation model for calculating fiber concrete elements is based on generally accepted preconditions. A hypothesis of plane cross sections is accepted as fair. The deformation diagram of compressed concrete is described by a nonlinear function with established parametric points. Distribution of stresses in stretched concrete is taken rectangular with corresponding coefficients which are taken depending on the type of deformation diagram. Determination of the carring capacity of fiber concrete elements occurs under extreme deformation criteria. Two cases of destruction of the investigated elements are considered. The first case is the destruction due to the achievement of limiting deformations in the concrete of the compressed zone with the simultaneous achievement of the fluidity limit in the working reinforcement. The second case is the destruction due to the achievement of limiting deformations in the concrete of the compressed zone without reaching the fluidity limit in the working reinforcement. Both cases of calculation are reduced to one functional dependence. This avoids the delimitation of different calculation cases. The main no dimensional modifier is the mechanical coefficient of reinforcement. According to the developed method, examples of calculations of reinforced concrete, fiber reinforced concrete elements and fiber concrete elements with longitudinal reinforcement are executed. The possibility of a spread variant design of reinforced concrete and fiber concrete elements is shown.Â